Subjektivitas Perempuan dalam Cerpen âCenanaâ Karya Oka Rusmini - Rojak, Mohamad Abdul; Rahayu, Lina Meilinawati; Priyatna, Aquarini (JURNAL PESONA, 2017)
AbstractÂ This paper examines female subjectivity contained in the short-story